Molecular species delimitation and description of a new species of Phenacogaster (Teleostei, Characidae) from the southern Amazon basin - Souza, Camila S. [UNESP]; Mattox, George M. T.; Vita, George; Ochoa, Luz E.; Melo, Bruno F.; Oliveira, Claudio [UNESP] (Pensoft Publishers, 2023)
Phenacogaster is the most species-rich genus of the subfamily Characinae with 23 valid species broadly distribut-ed in riverine systems of South America. Despite the taxonomic diversity of the genus, little has been advanced about its molecular diversity. A recent molecular phylogeny indicated the presence of undescribed species with-in Phenacogaster that is formally described here. We sampled 73 specimens of Phenacogaster and sequenced the mitochondrial cytochrome c oxidase subunit I (COI) gene in order to undertake species delimitation analyses and evaluate their intra-and interspecific genetic diversity. The results show the presence of 14 species, 13 of which are valid and one undescribed. The new species is known from the tributaries of the Xingu basin, the Rio das Mortes of the Araguaia basin, and the Rio Teles Pires of the Tapajós basin. It is distinguished by the incom-plete lateral line, position of the humeral blotch near the pseudotympanum, and shape of the caudal-peduncle blotch. Meristic data and genetic differentiation relative to other Phenacogaster species represent strong evidence for the recognition of the new species and highlight the occurrence of an additional lineage of P. franciscoensis.
Keywords: Biodiversity; Characinae; mitochondrial DNA; Neotropical freshwater fishes; Phenacogasterini